Improved fertilization efficiency of manure compost obtained by using oil shale semicoke as the bulking agent. (15th December 2022) - Li, Xu; Shi, Xiaoshuang; Lu, Mingyi; Guo, Rongbo; Feng, Quan
Abstract: Oil shale semicoke is a kind of solid waste produced during the retorting process of oil shale, which could cause environmental pollution without reasonable disposing. In our previous study, the abandoned semicoke was recycled as bulking agent to reduce the nitrogen loss and greenhouse gases emission during composting. But influences of the obtained semicoke-blended compost on soil properties and plant growth remained unclear, which would be discussed in this study. Through leaching experiments, it was found that the N/P/K retention capacity of soil mixed with semicoke-blended compost significantly increased for the good nutrients sorption capacity of oil shale semicoke. Subsequently, germination test showed the germination index of semicoke-blended compost could attain 120%, implying its low phytotoxicity. And pot experiments exhibited the biomass of cress and Brassica rapa significantly increased by 2–4 times when applying semicoke-blended compost as fertilizer, exhibiting its great benefits to plants. For the increase of crop yield, it was closely related to their elevated nutrients uptake efficiency, also might be related to the improved soil microbial community and activity as the microbial analysis indicated. Finally, results of pollutant detection showed the concentration of polycyclic aromatic hydrocarbons, Cr, As, Cd and Pb in the mature semicoke-blended compost obtained through composting was 2.82, 95.30, 5.95, 0.34 and 14.45 mg kg −1 respectively, meeting the standard for soil application. The research suggests composting could be an effective method for the harmless disposing and resource recycling of oil shale semicoke waste. Graphical abstract: Image 1 Highlights: Semicoke-blended compost could increase the nutrients retention capacity of soil. Semicoke-blended compost could promote the N and K uptake efficiency of plants. The microbial condition was improved when amending semicoke-blended compost. Composted oil shale semicoke exhibited no environmental toxicity.